Power of Initiative and Immunity of Local Government in Federal Nepal - Shrestha, Amrit Kumar; Ghimire, Tara Nath (Researcher: A Research Journal of Culture and Society, 2020)
Traditionally, it was considered that federal and state governments are the primary two components of the federal system. Provisions relating to local governments were left in the hand of state governments. The recent concept of federalism accepts the local governments as third and integral tier of the federal system. However, federalism and decentralization are used in different meaning. Federalism means the division of power within the center and federal units whereas decentralization considers devolution of power to the local units. The history of the local government begins with the ancient regime in Nepal, and it continues till at present. This article analyzes whether Nepal's local governments are exercising autonomous powers in the new federal system. It examines the local governments' status and positions in light of Clark's theory of autonomy. It concludes that the local governments have vested a significant level of powers of initiative and immunity to being needed for an autonomous institution.